Religion and Family (European Journal of Behavioral Sciences, 2018)
The family institution and the factors influencing its education and strengthening are among the issues that have been considered seriously in religious teachings. There is a lot of moral and religious prayers in religious texts that the commitment to them strengthens and strengthens the family. The author of this article has tried to study and analyze the teachings and the purpose of this study is to achieve these teachings. Thus, in the beginning, a glance at the place of worship and belief in the family, and then, while listing the views of beliefs and practices, we explain the role of each of them. The writer’s method in his review was documentary, and by referring to the main texts of the teachings of Islam, he explained the problem.